Compound containing dibenzo and derivative groups thereof and OLED device containing compound

By using compounds containing dibenzo and its derivative groups as electron transport materials in OLED devices, the problem of low electron mobility is solved, and a smaller driving voltage, larger current efficiency and external quantum efficiency are achieved, and the device life is extended.

CN120230090APending Publication Date: 2025-07-01ANHUI JINGKAI ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311774197.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

The low electron mobility in existing OLED devices leads to imbalance in electron and hole injection, affecting device efficiency and life, and degrading performance at high temperatures.

Method used

Compounds containing dibenzo and its derivative groups are used as electron transport materials to optimize the structure and material combination of OLED devices, improve electron mobility, and achieve smaller driving voltage, higher current efficiency and external quantum efficiency through doping and layer thickness optimization.

Benefits of technology

It achieves a smaller driving voltage, greater current efficiency, greater external quantum efficiency and longer service life, improving the overall performance of OLED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120230090A_ABST
    Figure CN120230090A_ABST
Patent Text Reader

Abstract

The invention provides a compound containing dibenzo and derivative groups of the dibenzo and a general formula I and an OLED device containing the compound, when the compound containing the dibenzo and the derivative groups of the dibenzo and the derivative groups of the dibenzo and the derivative groups of the dibenzo and the derivative groups of the dibenzo and the derivative groups of the dibenzo and the derivative groups of the dibenzo and the derivative groups of the dibenzo and the derivative groups of the dibenzo and the derivative groups of the compound are applied to OLED display devices as electron and relatively small driving voltage and relatively long service life are considered. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photoelectrochemistry, and particularly relates to a compound containing dibenzo and its derivative groups and an OLED device comprising the same. Background Art

[0002] An organic light emitting device (OLED) is a self-luminous device that utilizes the principle that the recombination of holes injected from the anode and electrons injected from the cathode after applying an electric field can cause a substance to emit light. Compared with traditional inorganic electroluminescent devices, OLED devices have the advantages of fast response, high luminous efficiency, self-luminescence, wide viewing angle, ultra-thin, good temperature adaptability, simple production process, and low energy consumption. They are gradually applied to flexible displays, flat panel displays, solid state lighting, and vehicle-mounted displays, and have great potential to replace mainstream liquid crystal displays.

[0003] Traditional OLED devices have a sandwich-like configuration and include electrode material layers and organic functional materials sandwiched between different electrode material layers. Various different functional materials are stacked together according to their uses to jointly form an OLED device. In recent years, with the continuous innovation of organic electroluminescent technology, OLED devices have gradually evolved from the initial sandwich configuration into a complex structure composed of multiple functional layers. Taking a classic organic electroluminescent device as an example, its stacked structure includes a cathode, an anode, and an organic film layer located between the cathode and the anode. The organic film layer includes a light emitting layer, an electron transport layer, a hole transport layer, a hole injection layer, an electron injection layer, etc.

[0004] High-efficiency organic electroluminescent devices require low driving voltage, high current efficiency, high external quantum efficiency, and relatively good stability. A low driving voltage enables the device to have a lower injection barrier; the higher the current efficiency, the higher the brightness generated by the device under a unit current; the higher the external quantum efficiency, the better the device performance. However, in organic semiconductor materials, the hole mobility is usually much higher than the electron mobility (generally, the electron mobility is 2-3 orders of magnitude lower than the hole mobility), which will lead to an imbalance in the injection of electrons and holes in the light emitting layer of the OLED device. Moreover, due to the large difference in the mobilities of electrons and holes, the light emitting region is likely to be close to the electron transport layer and the cathode side with smaller mobility, causing exciton quenching, thereby reducing the efficiency and brightness of the OLED device and affecting the comprehensive performance such as the driving voltage, current efficiency, and external quantum efficiency of the device. Therefore, how to improve the electron mobility of electron transport materials is an urgent problem to be solved in this field.

[0005] Meanwhile, when an organic electroluminescent device is driven at high temperatures, problems such as an increase in driving voltage, a decrease in luminous efficiency, and a shortening of lifespan usually occur, resulting in a decline in the performance of the organic electroluminescent device.

[0006] Therefore, in order to fabricate high-performance OLED devices, various organic functional materials are required to have good optoelectronic properties. For example, charge injection and transport materials are required to have good carrier mobilities and high glass transition temperatures, etc., and host luminescent materials are required to have good bipolarity, as well as appropriate HOMO / LUMO energy levels, etc.

[0007] In view of the current industrial application requirements of OLED devices, as well as the optoelectronic property requirements of different functional film layers and devices of OLED devices, more suitable and higher-performance OLED functional materials or combinations of functional materials must be selected in order to achieve the comprehensive characteristics of high efficiency, long lifespan, and low voltage of OLED devices. In terms of the actual requirements of the current OLED lighting industry, the development of current OLED materials is far from sufficient and lags behind the requirements of panel manufacturing enterprises. Therefore, the development of various functional layer materials remains an urgent problem to be solved. Summary of the Invention

[0008] Object of the Invention: The object of the present invention is to provide a compound containing a dibenzo and its derivative groups, which, when used as an electron transport material in an OLED display device, has a small current efficiency, a large external quantum efficiency, and takes into account a small driving voltage and a long service life.

[0009] Another aspect of the present invention provides an OLED display device.

[0010] Technical Solution: In order to achieve the above object of the invention, the present invention provides a compound of general formula I containing a dibenzo and its derivative groups:

[0011]

[0012] Wherein,

[0013] Ring represents Wherein, one or more -H in the foregoing groups may be independently replaced by -D (deuterium), -T (tritium), -CN, -F, -Cl, halogenated or unhalogenated alkyl containing 1-5 carbon atoms, or halogenated or unhalogenated alkoxy containing 1-5 carbon atoms respectively, and one or more -CH= in the rings may be independently replaced by -N=; and

[0014] Ring and Ring each independently represents Wherein, One or more of the -H in it may be independently replaced by -D, -T, -CN, -F, -Cl, a halogenated or unhalogenated alkyl group having 1 to 5 carbon atoms, or a halogenated or unhalogenated alkoxy group having 1 to 5 carbon atoms, and one or more of the -CH= in the rings may be independently replaced by -N=,

[0015] wherein, * represents the connection site in the bonded structure.

[0016] In the present invention, in order to obtain a smaller current efficiency, a larger external quantum efficiency, and take into account a smaller driving voltage and a longer service life, the compound of general formula I of the present invention contains the group represented by Ar1.

[0017] In the present invention, a bond passing through a ring in a straight line means that the straight line can be connected to any carbon atom in the ring, such as which means that the ring can be

[0018] In some embodiments of the present invention, the compound of general formula I is selected from the group consisting of the following compounds:

[0019]

[0020]

[0021] In some embodiments of the present invention, the ring and the ring each independently represents

[0022] wherein, P represents D or T; preferably, the ring and the ring each independently represents

[0023] In some embodiments of the present invention, the compound of general formula I is selected from the group consisting of the following compounds:

[0024]

[0025]

[0026]

[0027]

[0028]

[0029]

[0030]

[0031]

[0032] On the other hand, the present invention provides an OLED device which sequentially includes a substrate / anode layer, an organic layer, and a cathode layer from bottom to top, wherein the organic layer contains at least one compound of General Formula I.

[0033] In some embodiments of the present invention, in order to improve the electron mobility of the compound of General Formula I and enable the OLED device containing the compound of General Formula I to have a lower driving voltage, higher current efficiency, and higher external quantum efficiency, preferably ring and ring are the same group, so that the compound of General Formula I has good structural symmetry.

[0034] In some embodiments of the present invention, the organic layer may include a hole injection layer (HIL), a hole transport layer (HTL), a hole injection-hole transport functional layer (a layer having both hole injection and hole transport functions), an electron blocking layer (EBL), a hole blocking layer (HBL), an electron transport layer (ETL), an electron injection layer (EIL), and a combination of one or at least two of an electron transport-electron injection functional layer (i.e., having both electron transport and electron injection functions), wherein the electron transport layer contains at least one compound of General Formula I.

[0035] In some embodiments of the present invention, the organic layer contains at least one electron transport layer. The electron transport layer can play a role in promoting electron transport. The material used in the electron transport layer is a material that advantageously receives electrons from the cathode and transports the electrons to the light-emitting layer. The electron transport material can be intrinsic (undoped) or doped, and doping can be used to enhance conductivity.

[0036] In some embodiments of the present invention, the material of the electron transport layer contains at least one compound of General Formula I. Preferably, it is a compound of General Formula I doped with Liq. The doping mass ratio of the compound of General Formula I to Liq is 1:(0.001 - 1). For example, it can be 1:0.001, 1:0.005, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.08, 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, wherein Liq is the following compound:

[0037]

[0038] In some embodiments of the present invention, the thickness of the electron transport layer is 1-80 nm (including any value and sub-range therebetween), for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm, 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm, 60 nm, 61 nm, 62 nm, 63 nm, 64 nm, 65 nm, 66 nm, 67 nm, 68 nm, 69 nm, 70 nm, 71 nm, 72 nm, 73 nm, 74 nm, 75 nm, 76 nm, 77 nm, 78 nm, 79 nm, 80 nm.

[0039] In some embodiments of the present invention, the substrate / anode preferably has a material with a high work function. For example, Ag, Pt, Au, indium zinc oxide (IZO), or indium tin oxide (ITO).

[0040] In some embodiments of the present invention, the thickness of the hole injection layer is 1-60 nm (including any value and sub-range therebetween), for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm, 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, 57 nm, 58 nm, 59 nm, 60 nm.

[0041] In some embodiments of the present invention, the material of the hole injection layer is one or a combination of at least two of the following compounds:

[0042]

[0043] In some embodiments of the present invention, the doping mass ratio of HAT to HI2 is 1:(0.001 - 1). For example, it can be 1:0.001, 1:0.005, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.08, 1:0.1, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1.

[0044] In the present invention, the material of the hole transport layer is a material that can receive holes from the substrate / anode layer or the hole injection layer and transport the holes to the light-emitting layer.

[0045] In some embodiments of the present invention, the material of the hole transport layer is one or a combination of at least two of the following compounds:

[0046]

[0047] In some embodiments of the present invention, the thickness of the hole transport layer is 1 - 55 nm (including any value and sub-range therebetween). For example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm, 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, or 55 nm.

[0048] In the present invention, the material of the light-emitting layer is a material that can emit visible light by receiving holes and electrons from the hole transport layer and the electron transport layer and combining the received holes and electrons. The light-emitting layer material is divided into a host material and a guest material, and the mass ratio of the host material to the guest material is 1:(0.001 - 1). For example, it can be 1:0.001, 1:0.005, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.08, 1:0.1, 1:0.2, 1:0.4, 1:0.6, 1:0.8, 1:1.

[0049] In some embodiments of the present invention, the host material of the light-emitting layer is one or a combination of at least two of the following compounds:

[0050]

[0051] In some embodiments of the present invention, the guest material of the light-emitting layer is the following compound:

[0052]

[0053] In some embodiments of the present invention, the thickness of the light-emitting layer is 1 - 55 nm (including any value and sub-range therebetween), for example, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, 31 nm, 32 nm, 33 nm, 34 nm, 35 nm, 36 nm, 37 nm, 38 nm, 39 nm, 40 nm, 41 nm, 42 nm, 43 nm, 44 nm, 45 nm, 46 nm, 47 nm, 48 nm, 49 nm, 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, or 55 nm. In some embodiments of the present invention, the thickness of the light-emitting layer is preferably 5 - 55 nm.

[0054] In the present invention, the electron injection layer is a layer that injects electrons from the electrode, preferably has the ability to transport electrons, has an electron injection effect from the cathode, an excellent electron injection effect on the light-emitting layer or the luminescent material, prevents the excitons generated in the light-emitting layer from migrating to the hole injection layer, and has excellent thin film forming ability.

[0055] In some embodiments of the present invention, the electron injection layer material can be

[0056] In some embodiments of the present invention, the thickness of the electron injection layer is 0.1 - 20 nm, for example, it can be 0.1 nm, 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, or 20 nm.

[0057] In the present invention, the cathode generally preferably uses a material with a small work function so that electrons can be smoothly injected into the organic material layer, and it can be Al, Ag:Mg, LiF / Al, or LiO2 / Al.

[0058] In some embodiments of the present invention, the thickness of the cathode can be 1 - 180 nm. For example, it can be 1 nm, 2 nm, 4 nm, 6 nm, 8 nm, 10 nm, 12 nm, 14 nm, 15 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 25 nm, 26 nm, 28 nm, 30 nm, 32 nm, 34 nm, 35 nm, 36 nm, 38 nm, 40 nm, 42 nm, 44 nm, 45 nm, 46 nm, 48 nm, 50 nm, 52 nm, 54 nm, 55 nm, 56 nm, 58 nm, 60 nm, 62 nm, 64 nm, 65 nm, 66 nm, 68 nm, 70 nm, 72 nm, 74 nm, 75 nm, 76 nm, 78 nm, 80 nm, 82 nm, 84 nm, 85 nm, 86 nm, 88 nm, 90 nm, 92 nm, 94 nm, 95 nm, 96 nm, 98 nm, 100 nm, 102 nm, 104 nm, 105 nm, 106 nm, 108 nm, 110 nm, 112 nm, 114 nm, 115 nm, 116 nm, 118 nm, 120 nm, 122 nm, 124 nm, 125 nm, 126 nm, 128 nm, 130 nm, 132 nm, 134 nm, 135 nm, 136 nm, 138 nm, 140 nm, 142 nm, 144 nm, 145 nm, 146 nm, 148 nm, 150 nm, 152 nm, 154 nm, 155 nm, 156 nm, 158 nm, 160 nm, 162 nm, 164 nm, 165 nm, 166 nm, 168 nm, 170 nm, 172 nm, 174 nm, 175 nm, 176 nm, 178 nm, 180 nm.

[0059] In some embodiments of the present invention, an OLED device provided by the present invention sequentially includes a substrate / anode layer, a first hole injection layer, a second hole injection layer, a first hole transport layer, a second hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a cathode layer from bottom to top. Among them, the electron transport layer contains at least one compound of general formula I.

[0060] Advantageous effects: When the compound containing dibenzo and its derivative groups of the present invention is used as an electron transport material in an OLED display device, it has a smaller driving voltage, a larger current efficiency, a larger external quantum efficiency, and a longer service life. Specific embodiments

[0061] The present invention will be described below in conjunction with specific implementation embodiments. It should be noted that the following embodiments are examples of the present invention, which are only used to illustrate the present invention and not to limit the present invention. Other combinations and various improvements within the concept of the present invention can be made without departing from the gist or scope of the present invention.

[0062] The compounds of the embodiments of the present invention can be synthesized with reference to the specific synthesis examples shown below. However, it should be noted that obtaining the compounds is not limited to the synthesis methods and raw materials used in the present invention. Those skilled in the art can also select other methods or routes to obtain the novel compounds of the present invention. According to the preparation methods provided in the following text of the present invention, those skilled in the art can also use known conventional means (such as further selecting suitable catalysts, solvents, determining appropriate reaction temperatures, times, material ratios, etc., which are not particularly limited in the present invention) to achieve the preparation of the compounds of general formula I. Unless otherwise specified, raw materials such as solvents, catalysts, and bases used in the preparation can be obtained through public commercial channels or synthesized by methods known in the art.

[0063] The structures and codes of the organic material layer compounds used in the following application examples and application comparative examples are shown in Table 1.

[0064] Table 1 Organic layer materials in Application Examples 1-7 and Comparative Example 1

[0065]

[0066]

[0067] Synthesis Example 1

[0068] Synthesis of the compound of formula I-2-1:

[0069]

[0070] Step 1. Synthesis of the compound of formula 2-1

[0071] In a reaction flask, 200 mmol of the compound of formula 1-1 (bromobenzene) was added and fully dissolved in 300 ml of tetrahydrofuran. After purging with nitrogen, the temperature was lowered to -80 to -70 °C. While maintaining the temperature at -80 to -70 °C, 104 ml of 2.5 M n-butyllithium was added dropwise. After the addition was complete, the reaction was carried out at -80 to -70 °C for 1 h. While maintaining the temperature at -80 to -70 °C, 300 mmol of triisopropyl borate was added dropwise. After the addition was complete, the reaction was carried out at -80 to -70 °C for 1 h, and then the temperature was naturally raised to room temperature and the reaction was carried out at room temperature for 1 h. The reaction was stopped, 100 ml of 10% dilute hydrochloric acid was added, and the mixture was stirred for 0.5 h, extracted, washed with water, concentrated, crystallized with petroleum ether, and dried to obtain 22.7 g of a white powder of the compound of formula 2-1, with a yield of 93% (calculated based on bromobenzene).

[0072] Step 2. Synthesis of the compound of Formula 4-1

[0073] In a reaction flask, 150 mmol of the compound of Formula 3-1 (3-bromoindole, CAS: 1484-27-1), 165 mmol of the compound of Formula 2-1, 300 mmol of potassium carbonate, and 0.75 mmol of palladium acetate were added and completely dissolved in 320 ml of an aqueous solution of toluene and ethanol (the volume ratio of toluene, ethanol, and water was 20:3:9). After purging with nitrogen, the mixture was refluxed for 2 h. After the raw materials were completely reacted, the reaction was stopped. The mixture was extracted, washed with water, dried, passed through a column, concentrated, crystallized, and the obtained solid was recrystallized with toluene and dried in an oven to obtain 25.2 g of a buff solid of the compound of Formula 4-1, with a yield of 87% (calculated based on 3-bromoindole).

[0074] Step 3. Synthesis of the compound of Formula I-2-1

[0075] In a reaction flask, 130 mmol of the compound of Formula 4-1, 65 mmol of the compound of Formula 5-1 (3,7-dibromo-dibenzo[b,d]furan, CAS: 67019-91-4), 260 mmol of sodium tert-butoxide, 0.65 mmol of X-Phos, and 0.325 mmol of Pd2(dba)3 were added and completely dissolved in 200 ml of toluene. After purging with nitrogen, the mixture was refluxed for 2 h. After the reaction was completed, the reaction was stopped. The reaction mixture was cooled to room temperature, water was added, and the mixture was filtered and washed with water. The obtained solid was slurried with ethanol, filtered, dried, dissolved in toluene, passed through a column, concentrated, crystallized, and filtered and dried to obtain 25.4 g of a yellow powder solid of the compound of Formula I-2-1, with a yield of 71% (calculated based on 3,7-dibromo-dibenzo[b,d]furan).

[0076] The compound of Formula I-2-1 was tested by LCMS, and the following data were obtained:

[0077] ESI-MS: C 40 H 26 N2O, standard molecular weight 550.65, test result 550.71 [M+];

[0078] Elemental analysis: C 40 H 26 N2O, theoretical values: C, 87.25; H, 4.76; N, 5.09; O, 2.91, measured values: C, 87.25; H, 4.76; N, 5.09; O, 2.91.

[0079] Synthesis Example 2

[0080] Synthesis of the compound of Formula I-2-2:

[0081]

[0082] Step 1. Synthesis of the compound of Formula 2-2

[0083] Add 150 mmol of the compound of Formula 3-1, 165 mmol of the compound of Formula 1-2 (3-pyridineboronic acid, CAS: 1692-25-7), 300 mmol of potassium carbonate, and 0.75 mmol of palladium acetate into a reaction flask, and dissolve them thoroughly in 320 ml of an aqueous solution of toluene and ethanol (the volume ratio of toluene, ethanol and water is 20:3:9). Replace the air with nitrogen, reflux for 2 h. After the raw materials are reacted completely, stop the reaction, extract, wash with water, dry, column chromatography, concentrate, crystallize, and recrystallize the obtained solid with toluene, then dry it to obtain 23.9 g of the yellow solid of the compound of Formula 2-2, with a yield of 82% (calculated based on 3-bromoindole).

[0084] Step 2. Synthesis of the compound of Formula I-2-2

[0085] Add 120 mmol of the compound of Formula 2-2, 60 mmol of the compound of Formula 5-1, 240 mmol of sodium tert-butoxide, 0.6 mmol of X-Phos, and 0.3 mmol of Pd2(dba)3 into a reaction flask, and dissolve them thoroughly in 200 ml of toluene. Replace the air with nitrogen, reflux for 2 h. After the reaction is completed, stop the reaction, cool the reactants to room temperature, add water, filter, wash with water, slurry the obtained solid with ethanol, filter and dry it, dissolve it with toluene, column chromatography, concentrate, crystallize, filter and dry to obtain 18.9 g of the yellow solid of the compound of Formula I-2-2, with a yield of 57% (calculated based on the compound of Formula 5-1).

[0086] The compound of Formula I-2-2 was tested by LCMS, and the data are as follows:

[0087] ESI-MS: C 38 H 24 N4O, standard molecular weight 552.62, test result 553.57 [M+H];

[0088] Elemental analysis: C 38 H 24 N4O, theoretical values: C, 82.59; H, 4.38; N, 10.14; O, 2.90, measured values: C, 82.60; H, 4.38; N, 10.15; O, 2.90.

[0089] Replace the compound of Formula 5-1 with 3,7-dibromodibenzothiophene (CAS: 83834-10-0), and use the same synthesis method as that of the compound of Formula I-2-2 to obtain the compound of Formula I-1-2.

[0090] The compound of Formula I-1-2 was tested by LCMS, and the data are as follows:

[0091] ESI-MS: C 38 H 24 N4S, standard molecular weight 568.69, test result 569.18 [M+H];

[0092] Elemental analysis: C 38 H 24 N4S, theoretical values: C, 80.26; H, 4.25; N, 9.85; S, 5.64, measured values: C, 80.27; H, 4.24; N, 9.84; S, 5.63.

[0093] Replace the compound of formula 5-1 with 2,7-dibromo-9,10-dihydrophenanthrene (CAS: 61650-86-0), and use the same synthesis method as the compound of formula I-2-2 to obtain the compound of formula I-6-2.

[0094] The compound of formula I-6-2 was tested by LCMS, and the data are as follows:

[0095] ESI-MS: C 40 H 28 N4, standard molecular weight 564.68, test result 564.51 [M+H];

[0096] Elemental analysis: C 40 H 28 N4, theoretical values: C, 85.08; H, 5.00; N, 9.92, measured values: C, 85.09; H, 5.00; N, 9.91.

[0097] Replace the compound of formula 5-1 with 2,7-dibromo-9-phenyl-9H-carbazole (CAS: 444796-09-2), and use the same synthesis method as the compound of formula I-2-2 to obtain the compound of formula I-8-2.

[0098] The compound of formula I-8-2 was tested by LCMS, and the data are as follows:

[0099] ESI-MS: C 44 H 31 N5, standard molecular weight 627.73, test result 628.22 [M+H];

[0100] Elemental analysis: C 44 H 31 N5, theoretical values: C, 84.19; H, 4.66; N, 11.16, measured values: C, 84.20; H, 4.38; N, 10.17; O, 2.90.

[0101] Synthesis Example 3

[0102] Synthesis of the compound of Formula I-2-8:

[0103] Step 1. Synthesis of the compound of Formula 2-3

[0104] In a reaction flask, add 200 mmol of the compound of Formula 1-3 (deuterated 7-2-bromonaphthalene, CAS: 1359833-48-9), dissolve it thoroughly in 400 ml of tetrahydrofuran, displace with nitrogen, cool to -80 to -70 °C, control the temperature at -80 to -70 °C and dropwise add 104 ml of 2.5 M n-butyllithium. After the addition is complete, react at -80 to -70 °C for 1 h. Control the temperature at -80 to -70 °C and dropwise add 300 mmol of triisopropyl borate. After the addition is complete, react at -80 to -70 °C for 1 h. Then naturally warm to room temperature and react at room temperature for 1 h. Stop the reaction, add 100 ml of 10% dilute hydrochloric acid, stir for 0.5 h, extract, wash with water, concentrate, add petroleum ether to crystallize, and dry to obtain 32.9 g of a white powder of the compound of Formula 2-3, with a yield of 92% (calculated based on bromobenzene).

[0105] Step 2. Synthesis of the compound of Formula 3-3

[0106] In a reaction flask, add 150 mmol of the compound of Formula 3-1, 165 mmol of the compound of Formula 2-3, 300 mmol of potassium carbonate, 0.75 mmol of palladium acetate, and dissolve them thoroughly in 320 ml of an aqueous solution of toluene and ethanol (the volume ratio of toluene, ethanol, and water is 20:3:9). Displace with nitrogen and reflux for 2 h. After the raw materials have reacted completely, stop the reaction, extract, wash with water, dry, column chromatograph, concentrate, crystallize, and recrystallize the obtained solid with toluene and dry to obtain 33.0 g of an earthy yellow solid of the compound of Formula 3-3, with a yield of 88% (calculated based on 3-bromoindole).

[0107] Step 3. Synthesis of the compound of Formula I-2-8

[0108] In a reaction flask, add 130 mmol of the compound of Formula 3-3, 65 mmol of the compound of Formula 5-1, 260 mmol of sodium tert-butoxide, 0.65 mmol of X-Phos, 0.325 mmol of Pd2(dba)3, and dissolve them thoroughly in 200 ml of toluene. Displace with nitrogen and reflux for 2 h. After the reaction is complete, stop the reaction, cool the reactants to room temperature, add water, filter, wash with water, slurry the obtained solid with ethanol, filter and dry, dissolve in toluene, column chromatograph, concentrate, crystallize, filter and dry to obtain 32.4 g of a yellow powder solid of the compound of Formula I-2-8, with a yield of 75% (calculated based on 3,7-dibromo-dibenzo[b,d]furan).

[0109] The compound of Formula I-2-8 was tested by LCMS, and the data are as follows:

[0110] ESI-MS: C48 H 16 D 14 N2O, standard molecular weight 664.85, test result 664.51 [M+];

[0111] Elemental analysis: C 48 H 16 D 14 N2O, theoretical values: C, 86.71; H, 6.67; N, 4.21; O, 2.41; measured values: C, 86.70; H, 6.67; N, 4.22; O, 2.41.

[0112] Synthesis Example 4

[0113] Synthesis of the compound of Formula I-4-2:

[0114]

[0115] Step 1. Synthesis of the compound of Formula 3-4

[0116] Add 200 mmol of the compound of Formula 1-4 (2-bromobiphenyl, CAS: 2052-07-5) to a reaction flask, dissolve it thoroughly in 380 ml of tetrahydrofuran, displace with nitrogen, cool to -80 to -70 °C, control the temperature at -80 to -70 °C and dropwise add 80 ml of 2.5 M n-butyllithium. After the addition is complete, react at -80 to -70 °C for 1 h. Control the temperature at -80 to -70 °C and add 140 mmol of the compound of Formula 2-4 (2,7-dibromo-9-fluorenone, CAS: 14348-75-5) in batches. After the addition is complete, react at -80 to -70 °C for 1 h, then naturally warm to room temperature and stop the reaction at room temperature after reacting for 1 h. Add 100 ml of 10% dilute hydrochloric acid, stir for 0.5 h, extract, wash with water, concentrate, add petroleum ether to crystallize, and dry to obtain the crude product of the compound of Formula 3-4. The crude product of the compound of Formula 3-4 is dissolved thoroughly in 700 ml of toluene, add 7 ml of concentrated sulfuric acid, react at 80 °C for 1 h, stop the reaction, add aqueous sodium bicarbonate solution to neutralize to neutral, wash with water, concentrate, and the obtained solid is purified by crystallization with toluene and dried to obtain 53.8 g of a pale white solid of the compound of Formula 5-4, with a yield of 81% (calculated based on 2,7-dibromo-9-fluorenone). Step 2. Synthesis of the compound of Formula I-4-2

[0117] In a reaction flask, 50 mmol of the compound of Formula 5-4, 100 mmol of the compound of Formula 3-1, 200 mmol of sodium tert-butoxide, 0.5 mmol of X-Phos, and 0.25 mmol of Pd2(dba)3 were added and fully dissolved in 240 ml of toluene. After purging with nitrogen, the mixture was refluxed for 2 h. After the reaction was completed, the reaction was stopped. The reactants were cooled to room temperature, water was added, and the mixture was filtered and washed with water. The obtained solid was slurried with ethanol, filtered, dried, dissolved in toluene, purified by column chromatography, concentrated, crystallized, and dried to obtain 25.9 g of a yellow solid of the compound of Formula I-4-2, with a yield of 74% (calculated based on the compound of Formula 3-1).

[0118] The compound of Formula I-4-2 was tested by LCMS, and the data obtained were as follows:

[0119] ESI-MS: C 51 H 32 N4, standard molecular weight 700.83, test result 701.67 [M+H];

[0120] Elemental analysis: C 51 H 32 N4, theoretical values: C, 87.40; H, 4.60; N, 7.99, measured values: C: 87.39; H: 4.60; N: 8.00.

[0121] Device Preparation Example 1

[0122] An OLED device was prepared, which, from bottom to top, successively included a substrate / anode layer 1, a first hole injection layer, a second hole injection layer, a first hole transport layer, a second hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a cathode layer.

[0123] The preparation method of the OLED device was as follows:

[0124] 1) A transparent conductive ITO glass substrate (with an anode on it) (China Southern Glass Group Co., Ltd.) was ultrasonically treated in a commercial cleaning agent, rinsed in deionized water, and then successively washed with ethanol, acetone, and deionized water, baked in a clean environment until all moisture was removed, cleaned with ultraviolet light and ozone, and then treated with oxygen plasma for 30 seconds;

[0125] 2) The glass substrate with the anode was placed in a vacuum chamber, evacuated, and 10 nm thick of HAT was evaporated on the ITO glass slide as the first hole injection layer at an evaporation rate of 0.1 nm / s;

[0126] 3) On the first hole injection layer, HAT doped with compound HI2 (the doping mass ratio of HAT to HI2 was 1:0.05) was evaporated to form a 50 nm thick second hole injection layer at an evaporation rate of 0.1 nm / s;

[0127] 4) Evaporate HT1 on the second hole injection layer to form a first hole transport layer with a thickness of 10 nm at an evaporation rate of 0.1 nm / s;

[0128] 5) Evaporate HT2 on the first hole transport layer to form a second hole transport layer with a thickness of 10 nm at an evaporation rate of 0.1 nm / s;

[0129] 6) Evaporate BH doped with BD (the doping mass ratio of BH to BD is 1:0.03) on the second hole transport layer to form a light-emitting layer with a thickness of 20 nm at an evaporation rate of 0.1 nm / s;

[0130] 7) Evaporate a compound of general formula I doped with Liq (the doping mass ratio of the compound of general formula I to Liq is 1:0.3) on the light-emitting layer to form an electron transport layer with a thickness of 20 nm at an evaporation rate of 0.1 nm / s;

[0131] 8) Evaporate Liq on the electron transport layer to form an electron injection layer with a thickness of 20 nm at an evaporation rate of 0.1 nm / s;

[0132] 9) Evaporate Al on the electron injection layer to form a cathode with a thickness of 150 nm at an evaporation rate of 0.1 nm / s.

[0133] Subsequently, the evaporated substrate is encapsulated. First, use a gluing device to coat the cleaned cover plate with UV glue, then move the coated cover plate to the lamination section, place the evaporated substrate on top of the cover plate, and finally laminate the substrate and the cover plate under the action of a laminating device, while completing the photo-curing of the UV glue.

[0134] Application Examples 1-7 and Comparative Example 1

[0135] Independently fill the compounds of formula I-2-1, formula I-2-2, formula I-2-8, formula I-1-2, formula I-4-2, formula I-6-2, and formula I-8-2 as the compounds of general formula I into the electron transport layer in Device Preparation Example 1 to construct Application Examples 1-7. Replace the compound of general formula I in Device Preparation Example 1 with the compound ETL as the electron transport material to construct Comparative Example 1, and conduct performance tests on them. The test results are shown in Table 2 below.

[0136] Table 2 Performance test data of Application Examples 1-7 and Comparative Example 1

[0137] Application Examples Driving Voltage (V) Current Efficiency (cd / A) External Quantum Efficiency (%) T95 (h) Example 1 5.78 8.3 6.3 45 Example 2 4.13 19.8 16.12 56 Example 3 5.63 9.8 8.11 61 Example 4 5.31 15.6 13.56 44 Example 5 4.98 12.4 10.08 48 Example 6 5.13 10.1 12.51 51 Example 7 4.01 18.6 17.23 58 Comparative Example 1 5.89 8.1 6.1 38

[0138] Among them, the driving voltage (unit: V), current efficiency (unit: cd / A), and external quantum efficiency (unit: %) are all measured using a Photo Research PR655 spectrometer under the condition that the luminous intensity is 1000 cd / cm 2 The test is carried out under this condition.

[0139] The test of T95 (unit: h) is carried out using a Jinghe D3000-96CH lifetime measuring instrument to measure the time when the brightness becomes 95% of the initial brightness at room temperature (27°C) under a current density of 30 mA / cm 2 The test of T95 (unit: h) is carried out using a Jinghe D3000-96CH lifetime measuring instrument to measure the time when the brightness becomes 95% of the initial brightness at room temperature (27°C) under a current density of 30 mA / cm

[0140] It can be seen from the comparison between the above Comparative Example 1 and Examples 1-7 that the compound of General Formula I of the present invention, as an electron transport layer material, when applied to an OLED device, has a small current efficiency, a large external quantum efficiency, and takes into account a small driving voltage and a long service life.

[0141] It can be seen from the data in Table 2 that when the compounds of Formula I-2-1, Formula I-2-2, Formula I-2-8, Formula I-1-2, Formula I-4-2, Formula I-6-2, and Formula I-8-2 are used as electron transport layer materials and applied to OLED devices, they have a small driving voltage, a large current efficiency, a large external quantum efficiency, and a long service life.

[0142] Especially when one or more -H in ring and ring are independently replaced by D respectively, when applied to an OLED display device, it has a relatively smaller driving voltage, a larger current efficiency, a larger external quantum efficiency, and a longer service life.

[0143] When one or more -CH= in ring and ring are replaced by -N=, when applied to an OLED display device, it has a relatively smaller driving voltage, a larger current efficiency, a larger external quantum efficiency, and a longer service life.

[0144] In this application, the synthesis method process is only an example. If there are discrepancies between the synthesis method description and the compound structure in the process, the compound structure in the written description of the synthesis method shall prevail.

[0145] The above embodiments are only for illustrating the technical concept and characteristics of the present invention, and the purpose is to enable those who are familiar with this technology to understand the content of the present invention and implement it. It cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be covered within the protection scope of the present invention.

Claims

1. A compound of general formula I containing dibenzo and its derivative groups: Wherein, Ring represent wherein one or more -H in the aforementioned groups may be independently replaced by -D, -T, -CN, -F, -Cl, a halogenated or unhalogenated alkyl group having 1 to 5 carbon atoms, or a halogenated or unhalogenated alkoxy group having 1 to 5 carbon atoms, and one or more -CH= in the rings may be independently replaced by -N=; and Ring and the ring each independently represents wherein one or more of the -H in can be independently substituted by -D, -T, -CN, -F, -Cl, a halogenated or unhalogenated alkyl group having 1 to 5 carbon atoms, or a halogenated or unhalogenated alkoxy group having 1 to 5 carbon atoms, and one or more of the -CH= in the one or more rings can be independently substituted by -N= Wherein, * represents the connection site in the bonded structure.

2. The compound according to claim 1, wherein The compound of general formula I is selected from the group consisting of the following compounds: and Preferably, the ring and the ring each independently represent Wherein, P represents -D or -T.

3. The compound according to claim 1, characterized in that, The compound of general formula I is selected from the group consisting of the following compounds:

4. An OLED device comprising the compound according to any one of claims 1-3, characterized in that, From bottom to top, it sequentially includes a substrate / anode layer, an organic layer, and a cathode layer, wherein the organic layer contains at least one compound of general formula I; Preferably, the organic layer may include a hole injection layer (HIL), a hole transport layer (HTL), a hole injection-hole transport functional layer (a layer with both hole injection and hole transport functions), an electron blocking layer (EBL), a hole blocking layer (HBL), an electron transport layer (ETL), an electron injection layer (EIL), and a combination of one or at least two of an electron transport-electron injection functional layer (i.e., a layer with both electron transport and electron injection functions), wherein the electron transport layer contains at least one compound of general formula I; Preferably, the OLED device sequentially includes a substrate / anode layer, a first hole injection layer, a second hole injection layer, a first hole transport layer, a second hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a cathode layer from bottom to top, wherein the electron transport layer contains at least one compound of general formula I.

5. The OLED device according to claim 4, characterized in that, The material of the electron transport layer contains at least one of the compounds of general formula I; Preferably, the material of the electron transport layer is a compound of general formula I doped with Liq; Preferably, the doping mass ratio of the compound of general formula I to Liq is 1:(0.001 - 1); Preferably, the thickness of the electron transport layer is 1 - 80 nm.

6. The OLED device according to claim 4, wherein The material of the substrate / anode is Ag, Pt, Au, indium zinc oxide (IZO), or indium tin oxide (ITO); Preferably, the cathode material is Al, Ag:Mg, LiF / Al or LiO2 / Al; Preferably, the thickness of the cathode can be 1 - 180 nm.

7. The OLED device according to claim 4, wherein, The thickness of the hole injection layer is 1 - 60 nm; Preferably, the material of the hole injection layer is one or a combination of at least two of the following compounds: Preferably, the doping mass ratio of HAT to HI2 is 1:(0.001 - 1).

8. The OLED device according to claim 4, wherein The material of the hole transport layer is one or a combination of at least two of the following compounds: The thickness of the hole transport layer is 1 - 55 nm.

9. The OLED device according to claim 4, wherein The light-emitting layer material is divided into a host material and a guest material, and the mass ratio of the host material to the guest material is 1:(0.001 - 1); Preferably, the host material of the light-emitting layer is one or a combination of at least two of the following compounds: and The guest material of the light-emitting layer is the following compound: and Preferably, the thickness of the light-emitting layer is 1 - 55 nm.

10. The OLED device according to claim 4, characterized in that, The material of the sub-injection layer can be Preferably, the thickness of the electron injection layer is 0.1 - 20 nm.